Towards an understanding of dispensationalism before John Nelson Darby : a transition from Disregard to Dialogue - Van der Merwe, J.M. (Johan Matthys) (University of Pretoria, 2024)
Thesis (MTh (Systematic and Historical Theology))--University of Pretoria, 2023.